2019
DOI: 10.4034/pboci.2019.191.20
|View full text |Cite
|
Sign up to set email alerts
|

Sweetness Taste Preference Levels and Their Relationship to the Nutritional and Dental Caries Patterns among Brazilian Preschool Children

Abstract: Objective: To evaluate the sweetness taste preference levels and their relationship with the nutritional and dental caries patterns among preschool children. Material and Methods: The participants of this cross-sectional study were 191 children aged 4 to 5 years, who were regularly attending public Child Education Centers of a city southern Brazil. Children's preference for sugar was evaluated by the Sweet Preference Inventory; caries prevalence, according to the World Health Organization criteria, and nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…After the selection process, only three articles were qualified for final analysis [Table 1]. These three studies were reported the United States of America, Brazil, and India respectively [9][10][11]. The sample size of the included studies ranges from 38 to 191 children [9][10][11].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After the selection process, only three articles were qualified for final analysis [Table 1]. These three studies were reported the United States of America, Brazil, and India respectively [9][10][11]. The sample size of the included studies ranges from 38 to 191 children [9][10][11].…”
Section: Resultsmentioning
confidence: 99%
“…These three studies were reported the United States of America, Brazil, and India respectively [9][10][11]. The sample size of the included studies ranges from 38 to 191 children [9][10][11]. The study setting involved was the dental clinic [9,11] and educational center [10].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations